2020
DOI: 10.21203/rs.3.rs-30179/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating a Technology-Mediated HPV Vaccination Awareness Intervention: A controlled, Quasi-Experimental Mixed Methods Study

Abstract: Background College-aged women and men are at increased risk of acquiring human papillomavirus (HPV) and are considered an important catch-up population for HPV vaccination. Technology provides an attractive platform for HPV vaccination interventions. Limited research has explored technology-mediated HPV vaccination awareness interventions aimed at college students. The purpose of this pilot study was to evaluate a novel, technology-mediated, social media-based intervention to promote HPV vaccination among coll… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…Similarly, one feasibility study delivered an HPV vaccine intervention to undergraduate students via Facebook and electronic news. The intervention increased students’ knowledge about HPV and the HPV vaccine but did not impact students’ vaccine uptake [ 32 ]. To our knowledge, only one intervention study has reported the role of social media in influencing vaccine uptake behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, one feasibility study delivered an HPV vaccine intervention to undergraduate students via Facebook and electronic news. The intervention increased students’ knowledge about HPV and the HPV vaccine but did not impact students’ vaccine uptake [ 32 ]. To our knowledge, only one intervention study has reported the role of social media in influencing vaccine uptake behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the southeastern United States by Brandt et al reported that the use of social media platforms, such as Facebook, helped increase the awareness of HPV vaccination. 35 Given that social media platforms are simple and easy to use, 35 these platforms can be leveraged to increase awareness about HPV and cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This study included the implementation and evaluation of a 3-month online training designed to cultivate HPV vaccination champions. The intervention was adapted from a successful theory-based, technology-mediated HPV vaccination awareness intervention for college students ( 29 ). Recruitment methods are described below.…”
Section: Methodsmentioning
confidence: 99%
“…The development of the intervention was informed by best practices in implementation science ( 26 , 30 ) and based on a successful technology-mediated HPV vaccination awareness intervention for college students ( 29 ). Messages and health education information were adapted for parents based on formative audience research ( 8 , 31 , 32 ).…”
Section: Methodsmentioning
confidence: 99%